PENGARUH AUDIO VISUAL KESEHATAN REPRODUKSI TERHADAP PENGETAHUAN MENARCHE PADA REMAJA PUTRI DI MI NURUL ISLAM 01 KARANGANOM: PENGARUH MEDIA AUDIO VISUAL KESEHATAN REPRODUKSI TERHADAP PENGETAHUAN MENARCHE PADA REMAJA PUTRI DI MI NURUL ISLAM 01 KARANGANOM - Syafiatul Maghfiroh; Tut Rayani Aksohini Wijayanti; Rifzul Maulina (Jurnal Kesehatan Hesti Wira Sakti, 2024)
Background: Appropriate knowledge about menarche and reproductive health is crucial for young women to cope well with these changes. The use of audio-visual media in reproductive health education is a relevant and important research subject. This study aims to determine the effect of audio-visual reproductive health on knowledge of menarche among young women at MI Nurul Islam 01 Karanganom. Method: The type of research that will be used in this research is using the pre-experimental design method with the type of pre test and post test one group design. The total sample was 37 respondents using a Purposive Sampling sampling technique. The research instrument used audio visuals on reproductive health and level of knowledge. Data were analyzed using the Wilcoxon sign rank test. Result: The research results showed that before being given audio visuals, the majority had good knowledge, 22 respondents (59.5%) and after being given audio visuals, 34 respondents (91.9%) had good knowledge. The results of the analysis obtained a p-value of 0.001 < α=0.05, meaning it is significant. Conclusion: The results of the research show that audio visual education is effective in increasing knowledge of reproductive health among young women at MI Nurul Islam 01 Karanganom.